PENGARUH KECANGGIHAN TEKNOLOGI INFORMASI DAN PENGETAHUAN KARYAWAN BAGIAN AKUNTANSI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI - Utomo, Langgeng Prasetyo (STIE PGRI Dewantara Jombang, 2019)
This study aimed to determine the effect of sophisticated of information technology and accounting employee?s knowledge of the effectiveness of accounting information systems. Effectiveness of the accounting information system is a success achieved by the accounting information system to produce timely, accurate, and reliable. Collecting data in this study using field survey by distributing questionnaires. The questionnaire submitted to the manager and finance employee?s Republic of Indonesian Employee Coorperative in Jombang city. The sampling that is saturated sampling and analysis using multiple linear regression analysis. The results show of sophisticated of information technology and accounting employee?s knowledge positive and significant of the effectiveness of accounting information systems.